KOMPARASI PRAKTIKUM RIIL DAN PRAKTIKUM VIRTUALTERHADAP HASIL BELAJAR KIMIA SISWA SMA PADA PEMBELAJARAN LARUTAN PENYANGGA - Agustina Dewi; Nyoman Tika; I Nyoman Suardana (Jurnal Pendidikan Kimia Indonesia, 2019)
ABSTRAKPenelitian ini bertujuan mendeskripsikan dan menjelaskan perbedaan hasil belajar kimia, antara siswa yang mengikuti pembelajaran dengan praktikum riil dan virtual. Penelitian ini merupakan eksperimen semu dengan rancangan non equivalent pretest-posttest control group design. Populasi penelitian adalah siswa kelas XI IPA SMA Laboratorium Undiksha Singaraja tahun ajaran 2017/2018. Sampel penelitian ini adalah siswa kelas XI IPA 1 sebagai kelas eksperimen dan siswa kelas XI IPA 2 sebagai kelas kontrol yang dipilih dengan teknik cluster random sampling. Siswa kelas eksperimen dibelajarkan dengan praktikum virtual dan siswa di kelas kontrol dibelajarkan dengan praktikum riil. Data dianalisis dengan teknik analisis deskriptif dan inferensial. Analisis deskriptif hasil belajar kimia siswa dideskripsikan berupa skor rata-rata pre-test dan post-test siswa. Analisis inferensial hasil belajar kimia siswa menggunakan analisis kovarian (Anakova). Hasil uji Anakova menunjukkan nilai signifikansi sebesar 0,041, yang artinya terdapat perbedaan yang signifikan hasil belajar siswa yang dibelajarkan dengan praktikum riil dan virtual. Skor rata-rata hasil belajar siswa di kelas kontrol (81,55) lebih baik dibandingkan dengan kelas eksperimen (79,22). Kata kunci: hasil belajar kimia, praktikum riil, praktikum virtual. ABSTRACTThis research was aimed to describe and explain the differences of high school student’s achievement between students who followed learning process with real practicum and virtual practicum. The research was conducted on the topic of buffer. It is a quasi-experiment research with nonequivalent pre-test post-test control group design. The population was the student of class XI IPA SMA Laboratorium Undiksha on academic year 2017/2018. The samples were the students of XI IPA 1 class as experimental class and the students of XI IPA 2 class as control class that selected with cluster random sampling technique.The students in the experimental class followed the learning process with virtual practicum and the student in control class followed the learning process with real practicum. The data of chemistry student’s achievement were collected using the student achievement test. The data were analyzed with descriptive and inferential analysis.Descriptive analysis of chemistry student’s achievement were described in the form of the mean score of student’s pre-test and post-test. Inferential analysis of chemistry student’s achievement were analyzed using covarian analysis (Anacova). The Anacova test result showed the significant level on 0,041, which shown there were the significant differences of High school student’s achievement between the student who followed learning process with real practicum and virtual practicum. The mean score of student’s achievement in control class (81,55) was higher than experimental class (79,22)..Keywords: chemistry student’s achievemen, real practicum, virtual practicumt.